Building climate change adaptation indicator set for Moc Hoa district, Long An province - Nguyen , Thi Tinh Au (Journal of Technical Education Science, 2021)
To date, work in the field of climate change adaptation has resulted in many strategies for adaptation. In Vietnam, there have been many climate change adaptation activities implemented but has not been evaluated fully on effectiveness so that we can modify or make a replica of them systematically. In order to evaluate the effectiveness of carried out climate change adaptation activities, it is necessary to assess the current status of climate change adaptation for each local. In this paper, a set of CCA status evaluation indicators was developed and appreciated for Moc Hoa district, Long An province, to support a comprehensive assessment of the adaptation ability of this study area, the validity of investment resources allocation, and vulnerability to expose suitable policies. This set includes three indicators which are natural environment resilience, climate change vulnerability and climate change risk mitigation. The results showed that the environmental resilience indicators and the risk mitigation indicators were arranged at the medium level, while the climate change vulnerability indicators were high.